Multiple colorectal adenomas, classic adenomatous polyposis, and germ-line mutations in MYH. - Sieber, O; Lipton, L; Crabtree, M; Heinimann, K; Fidalgo, P; Phillips, R; Bisgaard, M; Orntoft, T; Aaltonen, L; Hodgson, S; Thomas, H; Tomlinson, I (2003)
BACKGROUND: Germ-line mutations in the base-excision-repair gene MYH have been associated with recessive inheritance of multiple colorectal adenomas. Tumors from affected persons displayed excess somatic transversions of a guanine-cytosine pair to a thymine-adenine pair (G:C-->T:A) in the APC gene. METHODS: We screened for germ-line MYH mutations in 152 patients with multiple (3 to 100) colorectal adenomas and 107 APC-mutation-negative probands with classic familial adenomatous polyposis (>100 adenomas). Subgroups were analyzed for changes in the related genes MTH1 and OGG1. Adenomas were tested for somatic APC mutations. RESULTS: Six patients with multiple adenomas and eight patients with polyposis had biallelic germline MYH variants. Missense and protein-truncating mutations were found, and the spectrums of mutations were very similar in the two groups of patients. In the tumors of carriers of biallelic mutations, all somatic APC mutations were G:C-->T:A transversions. In the group with multiple adenomas, about one third of patients with more than 15 adenomas had biallelic MYH mutations. In the polyposis group, no patient with biallelic MYH mutations had severe disease (>1000 adenomas), but three had extracolonic disease. No clearly pathogenic MTH1 or OGG1 mutations were identified. CONCLUSIONS: Germ-line MYH mutations predispose persons to a recessive phenotype, multiple adenomas, or polyposis coli. For patients with about 15 or more colorectal adenomas--especially if no germ-line APC mutation has been identified and the family history is compatible with recessive inheritance--genetic testing of MYH is indicated for diagnosis and calculation of the level of risk in relatives. Clinical care of patients with biallelic MYH mutations should be similar to that of patients with classic or attenuated familial adenomatous polyposis.